Comprehensive evaluation of printing process parameters and tensile properties of coconut polypropylene filament composites in additive manufacturing - Muhammad, Noryani; Jamaludin, Mohd Aiman; Mustafa, Nuzaimah; Yusuf, Yusliza; Shaharuzaman, Mohd Adrinata; Razak, Nurul Hanim (Universiti Putra Malaysia Press, 2024)
The printing process parameters are important in producing coconut polypropylene (CcPP) products by filament composite in the additive manufacturing industry. Fused deposition modeling techniques in 3D printing applications have considered multiple parameters to meet good finishing parts. This study uses comprehensive measurements to identify the best printing parameter for evaluating the composite properties. Complete deposition, unwrapping, good finishing, and adequate heat are the qualitative printing process parameters used to finalize the optimum nozzle and bed temperature of the CcPP filament composite. The range between 50⁰C to 80⁰C and 225⁰C to 245⁰C for bed and nozzle temperatures were used to achieve a well surface and successful production. After multiple trials of printing the CcPP filament composite, the optimal bed and nozzle temperatures were found to be 80°C and 230°C, respectively. Two types of infill density were used to analyze the effect on the tensile properties of CcPP filament composite. The result showed that 50% infill density was higher for both 1% and 5% fiber loading than 25% infill density for tensile strength with 15.65 and 22.87 MPa compared to 12.93 and 16.59 MPa. The same pattern as the score of Young’s moduli of 50% infill density was higher than 25% infill density for 1% and 5% fiber loadings with 479.52 and 641.23 MPa compared to 400.17 and 493 MPa. Qualitative and quantitative measurements of printing process parameters and properties help reduce the time and cost and benefit 3D printer users in the industry.